Desenvolvimento e avaliação antimicrobiana de géis in situ carreados com óleo essencial de Lippia sidoides Cham - Dantas, Maria Vitoria Oliveira (2023)
INTRODUCTION: Surgical Site Infections are considered a recurrent problem in surgical interventions. In situ gels with antimicrobial release can contribute to minimize the problem. OBJECTIVE: To develop, carry out morphological and physicochemical characterizations and evaluate the antimicrobial activity of in situ gels of Poloxamer (P407) and Chitosan (Q) loaded with essential oil of Lippia sidoides Cham. (OELS). METHODOLOGY: The OELS was characterized by gas chromatography coupled to mass spectroscopy (GC-MS). The minimum inhibitory concentration (MIC) of OELS against Staphylococcus aureus (ATCC 15656), Escherichia coli (ATCC 25922) and Candida albicans (ATCC 76485) strains was determined. In situ gels loaded with OELS at concentrations of 1%, 0.5% and 0.25% were made with and without the addition of Q. Gels formulated without OELS and saline solution 0.9% were negative controls. Chlorhexidine 0.12% and Nystatin were positive controls. The gels were characterized by fourier transform infrared spectroscopy (FTIR), size analysis, polydispersion index (PDI), zeta potential (PZ), evaluation of Sol-Gel transition properties (Tsol-gel), rheological analysis, stability study for 30 days and antimicrobial activity. RESULTS: Thymol (57.85%) was the major component found in OELS. The OELS showed MIC of 256, 128 and 128 μg/mL against strains of S. aureus, E. coli and C. albicans, respectively. FTIR confirmed the incorporation of OELS to the gels. Mean particle size and PDI values increased in the presence of Q. Only formulations with Q showed positive PZ values. The gels showed temperatures (Tsol-gel) between 20 ± 1 °C to 28 ± 1 °C, with times (Tsol-gel) at 37 °C ranging from 18.76 ± 1.24 s to 46.46 ± 8.89 s. According to the rheological analyses, the in situ gels present a pseudoplastic behavior, they are thermally stable in the residual temperature range (25-40 °C). The gels were stable within 30 days. The gel containing the OELS showed a MIC of 5 μg/mL against the symptom strains. CONCLUSION: The P407+Q in situ gels loaded with OELS showed stable characteristics, with promising antimicrobial action for application in the oral mucosa.